Xenophobic violence in Sweden 2009-2022 - Törnberg, Anton; Lundstedt, Måns; Vallström, Victoria; Wahlström, Mattias (University of Gothenburg, 2026)
This dataset contains all police-reported and hate-crime–flagged incidents of xenophobic physical violence recorded in Sweden between 1 January 2009 and 31 December 2022. It is a nationally complete event-level dataset comprising 2,522 unique police reports. The data material includes only cases involving actual or attempted physical violence where a xenophobic motive was either explicitly expressed or clearly inferable from the police narrative. Non-violent offences, harassment, threats, symbolic hate expressions, and other hate-crime categories are not included.

The dataset is constructed from structured and unstructured fields in Swedish police reports. Standardized variables (e.g., offence codes, timestamps, and reporting metadata) were extracted programmatically, primarily using Python scripts. Free-text descriptions were manually reviewed to classify motives, locations, and offender/victim characteristics. Several analytic variables were created by combining multiple fields (e.g., collapsed offence categories, derived motive groups, temporal variables). Strict exclusion criteria were applied to remove misclassified cases, unclear motives, incidents involving professional enforcement personnel, and intergroup conflicts not tied to xenophobic targeting. All coding procedures and variable definitions are documented in an accompanying codebook.

The dataset consists of 26 variables grouped into six domains:
1. Metadata (e.g., report date, reporting method)
2. Offence characteristics (official offence codes, collapsed offence categories, hate-crime motive)
3. Contextual information (incident date and time, physical setting, coordinates aggregated to 1×1 km grid cells, municipality and region)
4. Victim characteristics (age category, gender)
5. Offender characteristics (number of offenders, gender)
6. Type of violence (type of physical action and weapons/objects used)

The dataset is provided as a de-identified, row-level event file. Free-text narratives and personal identifiers have been removed to comply with ethical and legal requirements; geographical information is aggregated to grid level to reduce the risk of re-identification. No additional software beyond standard statistical tools (e.g., R, Python, Stata, SPSS) is required to read the file. Scripts used for automatic extraction and variable derivation can be supplied on request. A codebook describing all variables, coding decisions, and exclusion criteria accompanies the dataset.

This material enables researchers to examine long-term patterns, spatial and temporal distributions, and characteristics of xenophobic violence in Sweden using a transparent and replicable administrative-data framework.

Detta dataset innehåller alla polisanmälda och hatbrottsflaggade incidenter av främlingsfientlig fysisk våldsanvändning som registrerats i Sverige mellan 1 januari 2009 och 31 december 2022. Det är ett nationellt komplett dataset bestående av 2 522 unika polisanmälningar. Datamaterialet omfattar enbart fall som innefattar faktisk eller försök till fysisk våldsanvändning där ett främlingsfientligt motiv antingen uttryckligen framgår eller tydligt kan utläsas ur anmälan. Icke-våldsbrott, trakasserier, hot, symboliska hatuttryck och andra hatbrottskategorier ingår inte.

Datasetet är skapat utifrån både strukturerade och ostrukturerade fält i svenska polisanmälningar. Standardiserade variabler (t.ex. brottskoder, tidsstämplar och rapporteringsmetadata) har extraherats automatiskt, huvudsakligen med Python-skript. Narrativa fritextfält har manuellt granskats för att klassificera motiv, platser och offer- respektive gärningspersonsegenskaper. Flera analytiska variabler har konstruerats genom att kombinera information från flera fält (t.ex. sammanslagna brottskategorier, motivgrupper, tidsvariabler). Strikta exklusionskriterier har använts för att avlägsna felklassificerade fall, oklara motiv, händelser där yrkesutövare såsom polis eller ordningsvakter varit involverade i tjänsteutövning samt intergruppskonflikter som inte varit riktade mot en främlingsfientligt definierad målgrupp. Alla kodningsprocedurer och variabeldefinitioner finns dokumenterade i en medföljande kodbok.

Datasetet består av 26 variabler grupperade i sex domäner:
1. Metadata (t.ex. anmälningsdatum, rapporteringssätt)
2. Brottskarakteristika (officiella brottskoder, sammanslagna brottskategorier, hatbrottsmotiv)
3. Kontextuell information (händelsedatum och tid, fysisk miljö, koordinater aggregerade till 1×1 km-rutor, kommun och region)
4. Offervariabler (ålderskategori, kön)
5. Gärningspersonvariabler (antal gärningspersoner, kön)
6. Våldstyp (typ av fysisk handling samt använda vapen/objekt)

Datasetet tillhandahålls som en avidentifierad händelsefil på radnivå. Fritextmaterial och personuppgifter har tagits bort för att uppfylla etiska och juridiska krav; geografisk information har aggregerats till rutnivå för att minska risken för återidentifiering. Ingen särskild programvara krävs för att läsa filen utöver standardverktyg för statistisk analys (t.ex. R, Python, Stata, SPSS). Skript för automatisk extraktion och variabelhärledning kan tillhandahållas på begäran. En kodbok med beskrivningar av samtliga variabler, kodningsbeslut och exklusionskriterier följer datasetet.

Materialet gör det möjligt för forskare att analysera långsiktiga mönster, rumsliga och tidsmässiga fördelningar samt kännetecken för främlingsfientligt våld i Sverige på ett transparent och reproducerbart vis.
Främlingsfientligt våld i Sverige 2009-2022
Keywords: IMMIGRANTS; INVANDRARE; REFUGEES; FLYKTINGAR; CRIME AND SECURITY; BROTT; Xenophobic violence; Främlingsfientligt våld; Police reports; Polisanmälningar; Crime incidents; Brottsincidenter; hate crime; hatbrott; Crime and law enforcement; Kriminalitet och rättstillämpning; Political behaviour and attitudes; Politiska beteenden och attityder; Conflict, security and peace; Konflikter, säkerhet och fred; Equality, inequality and social exclusion; Jämlikhet, ojämlikhet och socialt utanförskap; Minorities; Minoriteter; Social behaviour and attitudes; Socialt beteende och attityder; Cultural and national identity; Kulturell och nationell identitet; Social Sciences; Samhällsvetenskap; Sociology; Sociologi; Political Science; Statsvetenskap; Criminology; Kriminologi